Comparison of maternal and umbilical cord blood soluble lectin-like oxidized low-density lipoprotein receptor 1 levels in early-and late-onset preeclampsia - Tuten, A.; Erman, H.; Korkmaz, G. G.; Oncul, M.; Gelisgen, R.; Sozer, V.; Acikgoz, S.; Simsek, G.; Uzun, H. (SPRINGER HEIDELBERG, 2014)
Background The main purpose of this study was to determine the maternal and umbilical cord blood oxidized LDL (oxLDL) and soluble lectin-like oxidized low-density lipoprotein receptor-1 (sLOX-1) levels in early-and late-onset preeclampsia (PE). Materials and methods A case-control study was conducted in pregnant women with early-onset (before 34 weeks' gestation n = 19) and late-onset (after 34 weeks' gestation n = 22) PE compared to healthy normotensive pregnant controls (n = 44). Groups were compared for the maternal and umbilical cord plasma oxLDL and serum sLOX-1 levels. Results The mean maternal and umbilical cord serum sLOX-1 and plasma oxLDL levels were significantly increased in early-and late-onset PE compared to controls (p < 0.001). When early-and late-onset PE women were compared with serum sLOX-1 levels, the increase was more pronounced in early PE (p < 0.001). However, same comparison is not statistically significant in cord blood for oxLDL where as it is significantly higher in maternal blood for oxLDL in early-onset PE group. Maternal and cord blood oxLDL and sLOX-1 levels are positively correlated with each other; however, they are negatively correlated with fetal weight and gestational age. Conclusions According to our results, maternal and umbilical cord blood levels of oxLDL and sLOX-1 were higher in preeclamptic pregnant. Thus, for the first time it has been shown that oxLDL and sLOX-1 levels were higher in fetal circulation as well as plasma of preeclamptic pregnant. However, sLOX-1 levels seem to be more implying than oxLDL for the differentiation of early and late preeclampsia.
Keywords: Early-onset preeclampsia; Late-onset preeclampsia; Soluble lectin-like oxidized LDL receptor-1; Oxidized LDL; LDL RECEPTOR-1; EXPRESSION; LOX-1; IDENTIFICATION; HYPERTENSION; PLACENTA; FORMS; Obstetrics & Gynecology